Surveying techniques for urban areas - Mishra A.; Agnihotri A.K.; Pipil S.; Gaur S.; Ohri A. (My University, 2025)
The field of surveying deals with spatial information about the locations on the Earth’s surface and serves as a base for establishing geographic information systems (GIS). Urban area mapping typically requires higher accuracy because high-rise building stability depends on greater precision. Surveying methods and tools include photogrammetry surveying equipment, terrestrial surveys, and satellite remote sensing for measurements of angles, azimuths, height differences, and distances on land. Modern surveying methods have largely replaced traditional surveying methods due to using satellites, global navigation satellite systems, and other advanced techniques in modern instruments. Total station, global positioning system (GPS), digital levels, and GIS in the urban geodetic survey are just a few examples of survey instruments that have greatly improved precision and measurement capability through electronic integration. Additionally, it has opened a new avenue, a more direct and accurate route for surveying. The current chapter focuses on the rapid developments in surveying in urban settings brought on by advancements in electronics and optics, which have significantly improved surveying instruments and methods. It also discusses the rapid changes that the surveying sector has undergone and the applicability of various urban surveying tools used on the ground and in unmanned aerial vehicles (UAV). UAV uses and practicality in highly congested urban river surveys are presented in a case study for the River Assi in Varanasi, India, where its implications for river restoration are also discussed. Some sophisticated methods, particularly deformation analysis in urban areas, are required for a thorough understanding of all the steps involved in the planning, performing, and analysing of the measurements. © 2024 Elsevier Ltd. All rights reserved.